Trudności w pracy nad przekładem fikcyjnej korespondencji Ksenofonta na język polski — analiza wybranych zagadnień - Marchewka, Anna (Collectanea Philologica, 2025)
The fictional correspondence of Xenophon has survived to our times in a fragmentary form, thanks to Stobaeus, whose Anthology contains excerpts from the Socratic letters. This correspondence is also part of the collection Socratis et Socraticorum Epistolae. Translating these texts poses significant challenges due to the peculiarities of the epistolary language, particularly its Atticization, as well as the presence of allusions and quotations that reflect the authors’ intellectual processes. The translator’s task, therefore, is to unveil the implicit knowledge embedded in the original text for the reader. This raises the question of what translation techniques should be employed to achieve this. Is a footnote always the only solution? How can one create a comprehensible and faithful translation for the modern reader of texts rooted in the Second Sophistic movement, which reference the realities of the classical era and Socratic thought – texts marked by a third culture? The article pays special attention to the Greek particle δέ, seen as a characteristic element of Attic speech, particularly in Xenophon’s language, as well as the dualis form.